Screening for Microbial Metal-Chelating Siderophores for the Removal of Metal Ions from Solutions - Marika Hofmann; Thomas Heine; Luise Malik; Sarah Hofmann; Kristin Joffroy; Christoph Helmut Rudi Senges; Julia Elisabeth Bandow; Dirk Tischler (Microorganisms, 2021)
To guarantee the supply of critical elements in the future, the development of new technologies is essential. Siderophores have high potential in the recovery and recycling of valuable metals due to their metal-chelating properties. Using the Chrome azurol S assay, 75 bacterial strains were screened to obtain a high-yield siderophore with the ability to complex valuable critical metal ions. The siderophore production of the four selected strains Nocardioides simplex 3E, Pseudomonas chlororaphis DSM 50083, Variovorax paradoxus EPS, and Rhodococcus erythropolis B7g was optimized, resulting in significantly increased siderophore production of N. simplex and R. erythropolis. Produced siderophore amounts and velocities were highly dependent on the carbon source. The genomes of N. simplex and P. chlororaphis were sequenced. Bioinformatical analyses revealed the occurrence of an achromobactin and a pyoverdine gene cluster in P. chlororaphis, a heterobactin and a requichelin gene cluster in R. erythropolis, and a desferrioxamine gene cluster in N. simplex. Finally, the results of the previous metal-binding screening were validated by a proof-of-concept development for the recovery of metal ions from aqueous solutions utilizing C18 columns functionalized with siderophores. We demonstrated the recovery of the critical metal ions V(III), Ga(III), and In(III) from mixed metal solutions with immobilized siderophores of N. simplex and R. erythropolis.